Early vitrectomy in the treatment of diabetic retinopathy - Fayzrakhmanov, R R; Shishkin, M M; Saraeva, S N (Vestnik oftal'mologii, 2025)
Proliferative diabetic retinopathy (PDR) remains a primary cause of blindness, as it can lead to tractional retinal detachment and vitreous hemorrhage. Although advanced treatments such as panretinal laser photocoagulation and anti-angiogenic therapy reduce the risk of vision loss, a substantial proportion of diabetic retinopathy cases may still progress to severe complications. With the advent of modern instruments, high-tech imaging systems, and minimally invasive vitrectomy techniques, surgical intervention should increasingly be considered as a preventive measure rather than a rescue therapy. This review highlights the evolution of vitreoretinal surgery for PDR and current advances in this field. Early vitrectomy, performed before the angiofibrotic shift and before the need for silicone oil tamponade, represents an additional option for preserving visual function.